Prática dialógico-problematizadora dos tutores na UAB/UFSM: fluência tecnológica no moodle - Schneider, Daniele da Rocha (2012)
The following research aimed to analyze whether the technological flow at Moodle boosts the problem-dialogic practice of the tutors at UAB/UFSM. According to the principles of school action-investigation and Freire s dialogic-problem, the concepts like interaction, interactivity, collaboration, and online monitoring are priority, since they constitute essential actions for technological flow. Operating with flow in order to understand, create, modify, and share is essential to figure out limit situations, enabling the problem-dialogic practice to emancipate Distance Learning students. Data has been obtained through the following steps: bibliographical study, participant observation, Moodle assessment research, survey. The delimitation, organization, and data analysis was conducted through methodological orientation of three matrices: Problem-Dialogic Matrix (MDP), Theme-Organizational Matrix (MTO), and Theme-analytical Matrix (MTA). The results of this investigation led to the practice of tutors of UAB/UFSM to reach the appropriate indexes for dialogic and problems concerning syllabus since technological flow is not limited to technical and practical standards only. Concluding, technological flow at Moodle boosts the dialogic when tutors practice goes both to technical and practical levels to independence.